Silica gel thin-layer chromatographic separation of cetylpyridinium chloride (CPC) from polyoxyethylene (20) sorbitan monolaurate (Tween-20) - Bhawani, Showkat Ahmad; Ali, Mohammad (Akadémiai Kiadó's, 2007)
Thin-layer chromatography of eleven cationic and non-ionic surfactants has been performed on silica gel layers with tetrahydrofuran (THF)-containing aqueous mobile phases. The mobile phase tetrahydrofuran–water 6:4 was identified as best for mutual separation of cetylpyridinium chloride (CPC) and polyoxyethylene (20) sorbitan monolaurate (Tween-20). The effect of the nature of the adsorbent (silica gel, alumina, or kieselguhr) on the mobility of the surfactants was examined and the comparative efficiency of each adsorbent was evaluated. The effect of metal cations as foreign substances on the mutual separation of CPC and Tween-20 was also examined. Limits of detection were determined for CPC and Tween-20 and semi quantitative determination of CPC was also attempted.